Screening and functional analysis of mutations in NEUROD1 gene in pedigrees of maturity-onset diabetes of the young - ZHANG Juan; GE Xiaoxu; ZHANG Rong; JIANG Fusong; JIANG Yanyan; LI Ming; LI Tiantian; LIU Chanwei; CHEN Yating; LIU Limei (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Objective·To screen the mutations of NEUROD1 gene in families of maturity-onset diabetes of the young (MODY), and investigate the correlation between the mutation and MODY6 and its potential pathogenesis in Chinese.Methods·PCR-direct sequencing was used for screening NEUROD1 mutations from 96 MODY probands who were negative for mutations in the GCK/MODY2, HNF1A/MODY3 and HNF1B/MODY5 genes, and the genotypic frequency of NEUROD1 variations were compared between the 96 MODY probands and 100 non-diabetic control subjects. A de novo modeling method was used to predict the three-dimensional (3D) structures of wild type (WT) and mutated NEUROD1 proteins. Transcriptional activities of both WT and mutant of NEUROD1 on insulin gene were detected by using dual luciferase reporter gene system.Results·Glu59Gln (NM_002500.5, c.175G>C), a heterozygous missense mutation in the NEUROD1 gene, was identified in a MODY pedigree. 3D structural analysis showed that the mutation transformed the negatively charged Glu59 of WT into uncharged mutation Gln59, leading to the loss of Glu59-Arg54 and Glu59-Lys88, two salt bridge bonds, and the formation of Gln59-Arg54, one new hydrogen bond. Transcriptional activity of Glu59Gln mutant for insulin gene was reduced by 36.3% when compared with that of WT (P<0.05). A common variation Ala45Thr (G-A) was identified, and AA+GA genotypic frequency of the variation was significantly elevated in the 96 MODY probands in comparison to non-diabetic control subjects (P=0.002).Conclusion·Glu59Gln mutation alters the N-terminal molecular conformation of NEUROD1 protein, resulting in decreased transcriptional activity of insulin gene, which is the cause of the defective insulin secretion in mutation carriers of the MODY6 pedigree. The Ala45Thr variation is associated with earlier age of onset of diabetes in MODY6 probands.